Combining metagenomics with metaproteomics and stable isotope probing reveals metabolic pathways used by a naturally occurring marine methylotroph. (21st July 2015) - Grob, Carolina; Taubert, Martin; Howat, Alexandra M.; Burns, Oliver J.; Dixon, Joanna L.; Richnow, Hans H.; Jehmlich, Nico; von Bergen, Martin; Chen, Yin; Murrell, J. Colin
Summary: A variety of culture‐independent techniques have been developed that can be used in conjunction with culture‐dependent physiological and metabolic studies of key microbial organisms in order to better understand how the activity of natural populations influences and regulates all major biogeochemical cycles. In this study, we combined deoxyribonucleic acid‐stable isotope probing (DNA‐SIP) with metagenomics and metaproteomics to characterize an uncultivated marine methylotroph that actively incorporated carbon from 13 C‐labeled methanol into biomass. By metagenomic sequencing of the heavy DNA, we retrieved virtually the whole genome of this bacterium and determined its metabolic potential. Through protein‐stable isotope probing, the RuMP cycle was established as the main carbon assimilation pathway, and the classical methanol dehydrogenase‐encoding gene mxaF, as well as three out of four identified xoxF homologues were found to be expressed. This proof‐of‐concept study is the first in which the culture‐independent techniques of DNA‐SIP and protein‐SIP have been used to characterize the metabolism of a naturally occurring Methylophaga ‐like bacterium in the marine environment (i.e. M ethylophaga thiooxydans L4) and thus provides a powerful approach to access the genome and proteome of uncultivated microbes involved in key processes in the environment.